Linear high-dimensional mediation models adjusting for confounders using propensity score method - Luo, Linghao; Yan, Yuting; Cui, Yidan; Yuan, Xin; Yu, Zhangsheng (Frontiers in Genetics, 2022)
High dimensional mediation analysis has been developed to study whether way of exposure to disease. However, most existing models are designed based on the assumption that there are no confounders between the exposure, the mediators, and the outcome. In practice, this assumption may not be feasible since high-dimensional mediation analysis (HIMA) tends to be observational where randomized controlled trial (RCT) cannot be conducted for some economic or ethic reasons. Thus, to deal with the confounders in HIMA cases, we proposed three propensity score related approaches named PSR (Propensity Score Regression), PSW (Propensity Score Weighting) and PSU (Propensity score Union) to adjust for the confounder bias in HIMA, and compared them with the traditional covariate regression method. The procedures mainly include four parts: calculating propensity score, sure independence screening, MCP (minimax concave penalty) variable selection and Joint-Significance testing. Simulation results show that the PSU model is the most recommended. Applying our models to the TCGA Lung cancer dataset, we find that smoking may lead to lung disease through the mediation effect of some specific DNA-methylation sites, including site Cg24480765 in gene RP11-347H15.2 and site Cg22051776 in gene KLF3.